Comparative study of the topical effectiveness of the andiroba oil (Carapa guianensis) and DEET 50% as repellent for Aedes sp - Miot, Hélio Amante [UNESP]; Batistella, Rafaelle Fernandes [UNESP]; Batista, Khristiani de Almeida [UNESP]; Volpato, Dimas Eduardo Carneiro [UNESP]; Augusto, Leonardo Silveira Teixeira [UNESP]; Madeira, Newton Goulart [UNESP]; Haddad Júnior, Vidal [UNESP]; Miot, Luciane Donida Bartoli [UNESP] (Instituto de Medicina Tropical, 2004)
O DEET (N, N-dietil-3-metilbenzamida) é hoje o repelente mais efetivo disponível, porém, seu uso pode apresentar importantes efeitos colaterais tópicos e sistêmicos. Alguns compostos botânicos, como a Andiroba (Carapa guianensis), têm demonstrado propriedades repelentes a um baixo custo e baixa toxicidade. Quatro voluntários hígidos submeteram seus antebraços recobertos com óleo de Andiroba a 100%, DEET 50% (controle positivo), óleo de soja refinado, óleo de Andiroba 15% e na ausência de produtos (controles negativos), diretamente a picadas de fêmeas saudáveis de Aedes sp. Foram aferidos os tempos da primeira e terceira picadas. Os resultados mostraram que a mediana da primeira picada nos antebraços sem produto foi 17.5s e a terceira picada, 40.0s. No óleo de soja, as picadas ocorreram em 60.0s e 101.5s. No óleo de Andiroba 100%, em 56.0s e 142.5s. Com Andiroba 15%, em 63.0s e 97.5s. Usando DEET 50% não houve picadas após 3600s na maioria dos experimentos (p < 0.001 Wilcoxon). O óleo de Andiroba 100% comparado ao óleo de soja, antebraço sem produto e óleo de Andiroba 15%, mostrou discreta superioridade (p < 0.001 Wilcoxon). Concluímos que o óleo puro de Andiroba apresenta efeito repelente discreto contra picada de Aedes sp., sendo significativamente inferior ao DEET 50%.

DEET (N,N-diethyl-3-methylbenzamide) is nowadays the most effective mosquito repellent available, however, its use can present some topical and systemic side effects. Some botanical compositions, as Andiroba (Carapa guianensis), have been proved repellent properties at low cost and toxicity. An experimental study was driven involving four volunteers submitting their forearms covered with Andiroba oil at 100%, DEET 50%, refined soy oil, Andiroba oil 15% and in the absence of products, directly to healthy females of Aedes sp. The times of first and third bites were checked. The results showed that the median of the first bite without any product was 17.5s and the third bite, 40.0s. In the soy oil, the bites happened in 60.0s and 101.5s, in the presence of Andiroba oil 100%, in 56.0s and 142.5s and in Andiroba oil 15%, in 63.0s and 97.5s. The volunteers using DEET 50% had not received bites after 3600s in most of the experiments (p < 0.001 Wilcoxon). Pure Andiroba oil compared to the soy oil, forearm without product and Andiroba oil 15%, showed discreet superiority (p < 0.001 Wilcoxon). Our conclusion is that this study demonstrated that the pure Andiroba oil presents discreet repellent effect against bite of Aedes sp., being significantly inferior to DEET 50%.
Estudo comparativo da eficácia tópica do óleo de andiroba (Carapa guianensis) e DEET 50% como repelente para Aedes sp
Keywords: Aedes; Insect repellent; DEET; Andiroba